Risk measures in strategic management research: auld lang syne? - Ruefli, Timothy W.; Collins, James M.; Lacugna, Joseph R. (Strategic Management Journal, 1999)
Risk is an integral component of strategic management decisions and often appears as an element of empirical studies reported in the strategic management literature. Recent methodological research in the financial economics and management science literatures has, however, raised serious questions about the strategic management literature’s two most widely used measures of firm and business-level risk: beta (or its derivatives) from the Capital Asset Pricing Model and simple variance (or its variants). This research reviews risk studies published in leading management journals in the past 15 years and summarizes the recent methodological findings in the adjacent literatures. We discuss the implications of these findings for our understanding of risk in strategic management and assess alternative measures of risk and conclude with a discussion of directions for future strategy research. Copyright © 1999 John Wiley & Sons, Ltd.